Efficacy and safety of low-dose clopidogrel after 12-month dual antiplatelet therapy for patients having drug-eluting stent implantation - Zhuang, Xiao-Dong; Long, Ming; Li, Cui-Ling; Hu, Cheng-Heng; Du, Zhi-Ming; Liao, Xin-Xue (Journal of Thoracic Disease, 2014)
Background: To prevent stent thrombosis (ST) after implantation of drug-eluting stents (DESs) in patients with coronary heart disease, 12-month dual antiplatelet therapy (DAPT) is recommended. However, the optimal long-term antiplatelet regimen is not clear for the patients who have completed the 12-month DAPT. Methods: We reviewed the data of 755 consecutive patients who had undergone percutaneous coronary intervention (PCI) three years ago and completed 12-month DAPT. They were divided into three groups according to the antiplatelet medication they had used for two years after 12-month DAPT [low-dose clopidogrel (Talcom®, 25mg/d), clopidogrel (Plavix®, 75mg/d) and aspirin (100 mg/d)]. The efficacy (a composite incidence of cardiac death, myocardial infarction and target vessel revascularization) and safety (incidences of bleeding, gastrointestinal trouble and drug discontinuation) were compared among the three groups. Results: The rates of multi-vessel lesions, prior MI, hemoglobin A1C (HbA1c) and low-density lipoprotein cholesterol were significantly higher in the clopidogrel (75 mg/day) group than in the other two groups (P>0.05 for both comparisons). There was no significant difference in the overall composite incidence of cardiac death, myocardial infarction and target vessel revascularization in the three groups at three years after PCI. The rates of bleeding (especially minor bleeding), gastrointestinal trouble, drug discontinuation and any blood transfusion were markedly lower in the low-dose clopidogrel (25 mg/d) group than in the other two treatment groups (P